Aproximaciones metodológicas al estudio de las migraciones internacionales - Díaz Matey , Gustavo (UNISCI Discussion Papers, 2007)
The aim of this work is to present the different methodological approaches to the study of international migrations - the economic theory, the historical structural approximation and the theory of the migrations system - to further enclose the different national policies on migration. It is obvious that there is a lack of theoretical and methodological debate over the international migrations, though this is an open field and the empty spaces are being covered. Nonetheless the studies over this topic in Spain are incipient and this is the main reason for the necessity of this kind of work.